Kajian katalogisasi subyek verbal di perpustakaan perguruan tinggi - Lilik Istiqoriyah (Al Maktabah, 2015)
This study examines the policy of verbal subject cataloging and its implementation in the college library. The main question of this study is how the verbal subject cataloging policy and its implementation in the process of cataloging activities in the college library. The data are taken from two college library which is considered to be fairly well established located around Jakarta. The methodology of this research is descriptive use a qualitative approach. The research reveals that the two libraries have already have policy on subject cataloging although it is still in a draft and still in the process of refinement. Both libraries have established guidelines for verbal subject cataloging which must be used consistently, but in its implementation there are many factors that affected the quality of the output of subject cataloging activities, including personal factors cataloger, the workload, the language of the library materials. It is recommended that the library to prepare a written policy adequately and maintain the consistency of the cataloging process and its output quality.